The six napoleons - Doyle, Conan Arthur; Alex Woolf (London: Arcturus, 2022)
Join world-famous detective Sherlock Holmes and his ever-loyal sidekick Dr. Watson as they embark on a daring adventure. Someone keeps breaking into shops and houses and smashing statuettes of the French general and statesman, Napoleon. Why? The police are baffled, so they call in the one man who can solve the mystery: London's greatest detective, Sherlock Holmes.